Communications, Information and Network Security 2003
DOI: 10.1007/978-1-4757-3789-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Critical Density Thresholds in Distributed Wireless Networks

Abstract: We present experimental and analytical results showing "zero-one" phase transitions for network connectivity, multi-path reliability, neighbor count, Hamiltonian cycle formation, multiple-clique formation, and probabilistic flooding. These transitions are characterized by critical density thresholds such that a global property exists with negligible probability on one side of the threshold, and exists with high probability on the other. We discuss the connections between these phase transitions and some known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…This typical modeling assumption is commonly used by many researchers [8], [12], [13], [22], [24], [25], [34], [49], [54], [55]. In particular, the initial placement of the nodes is assumed to be random when the sensors are distributed over a region from a moving vehicle such as an airplane.…”
mentioning
confidence: 99%
“…This typical modeling assumption is commonly used by many researchers [8], [12], [13], [22], [24], [25], [34], [49], [54], [55]. In particular, the initial placement of the nodes is assumed to be random when the sensors are distributed over a region from a moving vehicle such as an airplane.…”
mentioning
confidence: 99%
“…As for random graphs, aiming at applications to wireless networks, one of the main research topics in recent years has been the analysis of their connectivity (Santi, Blough, and Vainstein, 2001; Krishnamachari et al, 2002). In this paper, for the fixed radius model and the Bernoulli model, we demonstrated that the peak locations of H, E, and C almost coincide with each other at the phase transition area where the probability of existence of solutions (a sort of connectivity) rapidly decreases.…”
Section: Related Workmentioning
confidence: 72%
“…Reasonably, in the case R = 22m, a higher node density is required to reach this reachability. Detailed studies of critical density for wireless network connectivity can be found in [20], [21]. Here, we will focus on the comparison among different k-hop searching results.…”
Section: A Study Of Simple Geographic Greedy Routingmentioning
confidence: 99%